Analisis CSR Dan Kinerja Keuangan Studi Empiris Pada Perusahaan Yang Terdaftar Pada Indeks Sri Kehati - Farah Margaretha (Universitas Airlangga, 2012)
The objectives of this study are to analyze the difference and correlation between the corporate social performance and the corporate financial performance Companies in Indonesia, The sample population of this study is company listed in Indonesian Stock Exchange. sampling was used in this study, are 23 companies in SRI KEHATI Index The CSR score is measured by content analysis of corporate annual report . The data is tested by using partial correlation test to know the correlation between the corporate social performance and financial performance. The results of this study show that there no significant relation between financial performance at (t) year and CSR but found significant at tht (t+1) year. Managerial implications from this research will hopefully provide a new discourse for investor in considering the aspects that need to be taken into investments that are not to monetary measurements. this research hopes management company can provide the input on the importance of corporate social responsibility in terms of the overall strategic management to improve the company's financial and social performance and raise awareness of companies to conduct CSR activities.